Simplificação do processo de conversão de biomassa a etanol usando enzimas do meio fermentado integral de fungos filamentosos cultivados por fermentação em estado sólido - Pirota, Rosangela Donizete Perpetua Buzon (2013)
The main challenge on the conversion of lignocellulosic biomass into liquid fuels is the economic viability of this process. Thus, the commercialization of lignocellulosic ethanol is hindered mainly by the high costs of the enzyme preparations currently available cellulases - enzymes used in the saccharification step. Some strategies that can be adopted to reduce the enzymes costs include selecting microorganisms, use of cheaper raw materials and more efficient fermentation strategies such as the solid state fermentation (SSF) and efficient techniques for saccharification and fermentation. The aim this work was evaluate the use of the whole fermentation medium containing lignocellulosic biomass, fungal mycelium and enzymes in the hydrolysis of sugarcane bagasse pretreated by steam explosion for cellulosic ethanol production. In this context, a selection of filamentous fungi highly producing cellulases and hemicellulases, optimization operating conditions, such as humidity and temperature, were carried out for in house enzyme production using an instrumented bioreactor. Then, the efficiency of the whole fermentation medium and enzyme extract in enzymatic hydrolysis of lignocellulosic biomass for cellulosic ethanol production was evaluated. Among the 40 fungal strains evaluated, two strains of A. oryzae (P6B2 and P27C3A) stood out. In addition, one strain of A. niger 3T5B8 and another of T. reesei RUT C30 were also evaluated in this study. The influence of the substrate initial moisture content and temperature on efficiency of cellulase and xylanase production by strains of A. oryzae, A. niger and T. reesei grown in SSF under conditions of forced aeration and static were evaluated. The initial moisture content of the substrate did not affect the production of cellulases and xylanases by strain of A. oryzae P27C3A, however higher moisture was better for enzyme production by strains of A. oryzae P6B2 and A. niger and lower moisture were better for the production of cellulases and xylanases by T. reesei in both cultive systems. Temperature 28°C was best for xylanase production by all the fungal strains, while higher temperatures was better cellulases production in both culture systems. The use of whole fermented medium of A. niger or T. reesei obtained in the bioreactor were better in the hydrolysis sugarcane bagasse pretreated by steam explosion (BPSE) than the enzymatic extract with a final conversion of 41.3 and 24.9% of theoretical, respectively. The combination of whole fermentation medium of strains of A. oryzae (P6B2 or P27C3A) obtained in flasks and ½ commercial enzyme hydrolysis also were efficient on BPSE hydrolysis (26.1 and 42.4% of theoretical, respectively). Nevertheless, the combination of whole fermented medium of A. oryzae P6B2 and enzymatic extract of A. niger obtained in flasks promoted a conversion of 65% and an ethanol yield of 84% of the theoretical value. As overall conclusion it was found that the use of whole fermented medium produced by fungi cultivated under solid state fermentation (SSF) in the BPSE hydrolysis resulted in similar or higher yields compared to the hydrolysis using the enzyme extract, giving clear indication that the extraction/filtration step of the enzyme can be eliminated. The use of the enzyme complex of A. oryzae P6B2 in combination with the enzymes of A. niger resulted in a BPSE hydrolysis more efficient when compared with other combinations, showing the importance of selecting microorganisms for high enzymes production. Moreover, the use of a single reactor system for performing enzyme production steps by SSF, saccharification and alcoholic fermentation may be performed, avoiding the need for steps separation.